Blockholders and corporate monitoring costs: evidence from Malaysia - Mustapha, Mazlina; Che Ahmad, Ayoib (Faculty of Economics and Management, Universiti Putra Malaysia, 2013)
This paper examines the effect of outside block-holders’ ownership on the demand for corporate monitoring in relation to agency theory in the Malaysian business environment. The results of this study provide evidence that, given the cultural differences, the agents and the principals may act differently. The findings indicate that blockholders in Malaysia appear to demand more monitoring costs as their shareholdings increase. This positive relationship may be associated with the demand for more monitoring by minority shareholders as a balance against the power of the majority shareholders in the concentrated business environment in Malaysia and the tighten regulations after 1997/98 financial crisis. Further investigation shows that the institutional and non-institutional block-holders react and demand different level of monitoring costs. The institutional blockholders who are mostly government related institutions appear to demand more monitoring costs as their share ownership increase, while the non-institutional shareholders are associated with less monitoring costs as their shares increase.